Investment in higher education and its impact on the labor market: Applied Research in private colleges (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Investment in high education is considered to be most important factors of production which the return an individual and social than economic returns found by searching the growing problem of unemployment, especially among youth graduates, where the unemployment rate in 2010 (50%) of these high rates have led to increased migration of scientific minds graduate recently, "to search for job opportunities outside Iraq for not hiring functions and this is in vain" clear "in the human and financial resources lead to structural imbalances in the Iraqi economy.  When calculating the correlation coefficient between the graduates and the unemployment rate where it reached (0.21) emerged from the results of the analysis that the more number of students enrolled and graduates of whom the greater rates of unemployment in Iraq, especially "in terms of humanitarian and administrative, aspects  the permission of the alignment between undergraduate majors and needs of the labor market, while encouraging private sector investment in the field of technical education to achieve a balance between numbers of graduates and their terms of reference and the labor market.